Crossroads and Crises in the Religious Life of the Later Eleventh Century - Baker, Derek (Studies in church history, 1979)
It is fifty years since Germain Morin, in an article in the Revue Bénédictine articulated discussion of the tensions and developments in eleventh and early twelfth-century regular, and para-regular, life around a central ‘crisis of cenobitism’, and twenty years since Leclercq stabilised the debate in a wide ranging article which has become the basis of all subsequent comment. This crisis in the cenobitic life is now a commonplace, expressed in Leclercq’s terms as ‘the crisis of prosperity’ and answered by the resurgence of rural monasticism, eremitical in character, in reaction to the elaborate structures and relationships of an established monasticism resident in the urban centres of population and influence. The individual austerities and renunciations of Romuald stand at the beginning of a proliferating development in western Christendom, and may, in a general sense, be taken to characterise these new initiatives. The direct influence of Romualdine ideas and practices, whether through his foundations or through his self-proclaimed spiritual heir Damian, which is sometimes alleged is difficult to prove, but there is an obvious consonance between the Italian experiments and those elsewhere in the west, a compatibility of outlook and attitude between Romuald and Damian, and men like Bruno, Stephen Harding, Robert of Arbrissel.